Loss of CD28 expression associates with severe T-cell exhaustion in acute myeloid leukemia - Huang, Yueting; Zheng, Huijian; Zhu, Yuwen; Hong, Yan; Zha, Jie; Lin, Zhijuan; Li, Zhifeng; Wang, Caiyan; Fang, Zhihong; Yu, Xingxing; Liu, Long; Xu, Bing (Frontiers in Immunology, 2023)
Introduction Despite accumulated evidence in T-cell exhaustion in acute myeloid leukemia (AML), the immunotherapeutic targeting exhausted T cells such as programmed cell death protein 1 (PD-1) blockade in AML failed to achieve satisfying efficacy. Characteristics of exhausted T cells in AML remained to be explored. Methods Phenotypic analysis of T cells in bone marrow (BM) using flow cytometry combining senescent and exhausted markers was performed in de novo AML patients and healthy donors as well as AML patients with complete remission (CR). Functional analysis of T-cell subsets was also performed in de novo AML patients using flow cytometry. Results T cells experienced a phenotypic shift to terminal differentiation characterized by increased loss of CD28 expression and decrease of naïve T cells. Additionally, lack of CD28 expression could help define a severely exhausted subset from generally exhausted T cells (PD-1+TIGIT+). Moreover, CD28- subsets rather than CD28+ subsets predominantly contributed to the significant accumulation of PD-1+TIGIT+ T cells in AML patients. Further comparison of de novo and CR AML patients showed that T-cell exhaustion status was improved after disease remission, especially in CD28+ subsets. Notably, higher frequency of CD28-TIGIT-CD4+ T cells correlated with the presence of minimal residual disease in AML-CR group. However, the correlation between CD28- exhausted T cells and cytogenetic risk or white blood cell count was not observed, except for that CD28- exhausted CD4+ T cells correlated with lymphocyte counts. Intriguingly, larger amount of CD28-TGITI+CD8+ T cells at diagnosis was associated with poor treatment response and shorter leukemia free survival. Discussion In summary, lack of CD28 expression defined a severely exhausted status from exhausted T cells. Accumulation of CD28- exhausted T cells was linked to occurrence of AML, and correlated to poor clinical outcome. Our data might facilitate the development of combinatory strategies to improve the efficacy of PD-1 blockade in AML.